Development of a methodology for the evaluation of active safety using the example of preventive pedestrian protection doctoral thesis accepted by Technische Universität Berlin, Germany - Helmer, Thomas (Springer International Publishing, 2015)
The book reports on a new methodology for optimization and evaluation of traffic safety, which simulates the processes involved in traffic conflicts on the basis of detailed dynamical, human, and technical models. The models incorporate the whole spectrum of human cognitive functions and responses, the responses of an active safety system and the interactions between the human and the system as they occur in a sample of relevant traffic contexts. Using the developed method, the author was able to assess the reduction in accidents and injuries as well as the possible side effects resulting from a preventive pedestrian-protection system. The book provides practical solutions in the area of active safety systems. It represents an interesting source of information for researchers and professionals as well as all stakeholders, including policy makers and consumer advocates, with the common goal of promoting the implementation and adoption of highly efficient systems for preventing accidents and injuries.